Correction to: Gambling-related suicide in East African Community countries: evidence from press media reports - Mark Mohan Kaggwa; Mohammed A. Mamun; Sarah Maria Najjuka; Moses Muwanguzi; Moses Kule; Rahel Nkola; Alain Favina; Raymond Bernard Kihumuro; Gideon Munaru; Innocent Arinaitwe; Godfrey Zari Rukundo; Mark D. Griffiths (BMC, 2022)
An amendment to this paper has been published and can be accessed via the original article.